DYNAMICS OF PEDAGOGICAL CULTURE IN CONDITIONS OF SOCIAL TRANSFORMATION - Kirill B. Safonov (Russian Studies in Culture and Society)
The article is devoted to a comprehensive analysis of the phenomenon of pedagogical culture. It is noted that as the society transforms, the values and norms that are the determinants of the teacher’s activity are also subject to rethinking. Adapting to changes in the pedagogical culture makes it possible to increase the effectiveness of interaction with students, to optimize the effectiveness of work in the field of education.